The Adoption of Interorganizational Cost Management in a Vehicle Assembly Plant in the Greater Region of ABC - Faria, Ana Cristina de; Soares, Iderlan Charles; Rocha, Welington; Rossi, George Bedinelli (Review of Business Management, 2013)
It is necessary that organizations define strategies for cost management in interorganizational relationships existing in the Supply Chain (SC), focusing not only on reducing individual costs, but on improviving the competitive advantage of these chains. The Interorganizational Cost Management (ICM) focuses on minimizing costs, creating competitive advantages in relation to competing chains. The objective of this study was to check how the ICM has been applied in the chain of an automotive assembly plant in the Greater Region of ABC (state of São Paulo). In conducting the exploratory research, we inquired of 10 managers in the areas of Procurement, R&D, Supplier Quality Engineering, Logistics and Finance, to identify and analyze the aspects that characterize the practice of ICM in the assembly plant chain. We found that the ICM is adopted in all phases of the life cycle of the product, focused on cost reduction and continuous improvement of processes and products. The results show that the practice of ICM makes the relationships between the assembly plant and its suppliers more profitable and sustainable, and it is a tool capable of delivering benefits to the entire chain. Therefore, it should be included in the strategic management of companies.